AKUMULASI DAN DISTRIBUSI TIMBAL (Pb) PADA DUA JENIS TANAMAN SAYURAN DENGAN PENAMBAHAN EDTA - seli trisnawati; Anis Rosyidah; Mahayu Woro Lestari (AGRONISMA, 2020)
Lead metal in agriculture is one of the pollutants that accumulates a lot in the field due to residues of chemical fertilizers and pesticides. various efforts to clean up environmental pollution include bioremediation and phytoremediation. To increase the metal absorption can also be done by inducing the phyto-extraction process using chelate compounds. The chelate compound commonly used to improve the optimization of phytoremediation is EDTA (Ethylen Diamin Tetraacid). The study was conducted at the Greenhouse of the Faculty of Agriculture, Malang Islamic University, Lowokwaru District, Malang with a height of 540 meters above sea level and a temperature of 21 ÂºC - 30 ÂºC. The study was conducted in September-December 2019. The study was conducted experimentally and arranged using a Randomized Block Design (RBD) which was arranged factorially and consisted of 2 factors. Based on the results of statistical analysis shows that there is a real influence on EDTA treatment and plant types on TF value. Spinach plants showed a TF value> 1 and Spinach plants showed a value <1. TF value <1 indicates the occurrence of fitostabilization mechanism. Whereas TF> 1 shows the mechanism of phytoextraction. The value of TF (Translocation factor) is not influenced by the concentration of EDTA because plants have different abilities in translating metals from the canopy to the roots.